Smoking Frequency and Related Factors in A Military Factory in Ankara - Aksu, Eren Ekrem; Uğraş Dikmen, Asiye (Turkey Health Literacy Journal, 2022)
In this study, it was aimed to determine the relationship between the smoking frequency of the employees in a military factory and theeducational status of the people, their smoking and the age of starting smoking, and a questionnaire technique, which is one of the quantitative research methods, was applied to a total of 260 employees working in the factory. In the research, it was determined that 153 people (61.3%) working in the factory smoked. There is a statistically significant relationship between smoking and working time in the factory. According to this; The rate of smokers who work in the factory for more than 60 months is significantly higher than those who do not. There is a statistically significant relationship between smoking and educational status. Accordingly, it was found to be significantly higher in those with secondary education, associate degree/undergraduate degree, those with a family history of smoking, and those working alone. Employees strongly (50%) support anti-smoking laws and sanctions, and 42.4% think that the scope of the smokingcessation ban could be improved. The reasons for starting smoking were stated as 20% stress, 54.5% wannabe, 25.5% curiosity. Of the current smokers, 93 (60%) tried to quit smoking in the last year, while 62 (40%) did not try. It was revealed that 13 (27.7%) of the smokers and respondents who responded to the questionnaire were addicted to smoking, 22 (46.8%) continued due to habit, and 12 (25.5) due to stress. . Since the effect of being in the same environment and seniority in the profession is at the forefront in starting smoking and maintaining this behavior, smoking cessation campaigns should be planned for working groups rather than individuals. In addition, it was important to provide support to those who want to quit smoking by the occupational health and safety experts within the factory.